The Implementation of Sharia Principles Concept of Hotels - Dian Deliana (Universitas Pendidikan Ganesha, 2022)
Sharia lodging is a lodging sector business adapted to sharia principles in providing facilities and services. This study aims to determine the Implementation of the Concept of Hotel Sharia Principles. The method used is Literature Review using the Atlantis Press, Emerald, Taylor & Francis database and a search engine from Google Scholar. A literature search using predetermined inclusion and exclusion criteria. Extraction using PRISMA Flow Diagram. The research results were obtained from the extraction data from 96 articles to 9 articles. There are 4 themes, namely sharia hotel standards, Blue Ocean strategy, the concept of blessing, and Corporate social responsibility. the application of Sharia hotels is by Islamic economic values, namely following the principles of monotheism, justice, mashlahah, ta'awun and balance. Sharia hotels are needed to support the halal industry and facilitate the needs of Muslim tourists in traveling.